Influence of the inhomogeneity of porous media on the instantaneous compactification of the support of solution of the filtration problem - Degtyarev, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We study the phenomenon of instantaneous compactification and the initial behavior of the support of solution of the filtration equation for inhomogeneous porous media.